Invisible Craftsmanship: Lulesámi Women's Production of Handicraft and Well-Being at Home. (4th May 2019) - Gustafsson, Anna
Abstract: This paper looks at the contemporary role of handicraft among Lulesámi people, a subgroup of the indigenous Sámi, in Northern Norway. Many studies have addressed the changes in Sámi craftsmanship over time, its symbolic significance for Sámi culture and its recent commodification. By contrast, unpaid craft production at home has gained less attention. My ethnography addresses this gap and considers the significance of women's domestic craft production. While women's domestic work cannot easily be measured, this analysis shows that their craftsmanship plays an important part in creating personal and social well-being in everyday life. Paying attention to the demands of domestic handicraft made for non-commercial purposes provides novel insights into Sámi handicraft and the significance of women's domestic work in contemporary society.